Invisible Influence : The hidden forces that shape behaviour - Jonah Berger (Simon & Schuster UK Ltd, 2016)
Introduction -- Monkey see, monkey do -- A horse of a different color -- Not if they're doing it -- Similar but different -- Come on baby, light my fire -- Conclusion : putting social influence to work.